Dynamic regulation of the extracellular matrix in reward memory processes: a question of time - Valeri, Jake; Gisabella, Barbara; Pantazopoulos, Harry (Frontiers in Cellular Neuroscience, 2023)
Substance use disorders are a global health problem with increasing prevalence resulting in significant socioeconomic burden and increased mortality. Converging lines of evidence point to a critical role of brain extracellular matrix (ECM) molecules in the pathophysiology of substance use disorders. An increasing number of preclinical studies highlight the ECM as a promising target for development of novel cessation pharmacotherapies. The brain ECM is dynamically regulated during learning and memory processes, thus the time course of ECM alterations in substance use disorders is a critical factor that may impact interpretation of the current studies and development of pharmacological therapies. This review highlights the evidence for the involvement of ECM molecules in reward learning, including drug reward and natural reward such as food, as well as evidence regarding the pathophysiological state of the brain’s ECM in substance use disorders and metabolic disorders. We focus on the information regarding time-course and substance specific changes in ECM molecules and how this information can be leveraged for the development of therapeutic strategies.